Developing and Measuring the Impact of an Accounting Ethics Course that is Based on the Moral Philosophy of Adam Smith - Sorensen, Daniel P. (Journal of business ethics, 2017)
Accounting ethics failures have seized headlines and cost investors billions of dollars. Improvement of the ethical reasoning and behavior of accountants has become a key concern for the accounting profession and for higher education in accounting. Researchers have asked a number of questions, including what type of accounting ethics education intervention would be most effective for accounting students. Some researchers have proposed virtue ethics as an appropriate moral framework for accounting. This research tested whether Smithian virtue ethics training, based on Adam Smith’s “The Theory of Moral Sentiments” (1790/1976), is effective in improving accounting student’s cognitive moral development (CMD). This research used a pre-test, treatment, post-test, quasi-experimental design utilizing the Defining Issues Test 2 (DIT-2) instrument to measure students’ CMD. Analysis of DIT-2 gain scores did show a significant improvement in subjects’ personal interest scores and a significant improvement in an overall measure of CMD, the DIT N2 index, whereas their DIT-2 post-conventional scores did not improve significantly. This research supports the proposition that the concepts contained in Smithian virtue ethics can contribute to an effective accounting ethics education intervention. However, further research is required to determine what concepts should be included to improve accounting students’ post-conventional moral reasoning.